Short- and long-term outcomes of endoscopic papillary large balloon dilation with or without sphincterotomy for removal of large bile duct stones. (January 2013) - Kogure, Hirofumi; Tsujino, Takeshi; Isayama, Hiroyuki; Takahara, Naminatsu; Uchino, Rie; Hamada, Tsuyoshi; Miyabayashi, Koji; Mizuno, Suguru; Mohri, Dai; Yashima, Yoko; Kawakubo, Kazumichi; Sasaki, Takashi; et al.
Abstract Objective. Removal of large bile duct stones by endoscopic papillary large balloon dilation (EPLBD) with endoscopic sphincterotomy (EST) has been proven safe and effective. Little evidence supports the benefits of a preceding EST in reducing complications. Recent studies suggest that large bile duct stone removal by EPLBD alone may be safe and effective. Material and methods. We removed large bile duct stones by EPLBD with EST from March 2008 to February 2010 and without EST from March 2010 to October 2011. Efficacy and safety of EPLBD with or without EST and late biliary complication outcomes were assessed. Results. Forty-two patients (men/women, 27/15; mean age, 76 years) underwent EPLBD: 14 underwent EPLBD with EST and 28 underwent EPLBD without EST. The mean stone size was 14 mm (9–30 mm). Overall complete stone removal rate was 98%, with 83% achieved in 1 session. Complete duct clearance by EPLBD alone was achieved in 79%. Mechanical lithotripsy was required in 4 (10%) patients. Extracorporeal shock wave lithotripsy and electrohydraulic lithotripsy were required in 4 (10%) and 1 (2%) patients, respectively. Pancreatitis and perforation occurred in 2 (5%) and 1 (2%) patients, respectively. Patients treated by EPLBD with EST and by EPLBD alone did not differ in complication outcomes. Six (14%) patients had recurrent bile duct stones, with a significant correlation to dilated common bile duct (p = 0.0351). Conclusions. EPLBD is safe and effective in patients with large bile duct stones. Preceding EST may be unnecessary.